Upregulation of TGF-beta, FOXP3, and CD4+CD25+ regulatory T cells correlates with more rapid parasite growth in human malaria infection. - Walther, M; Tongren, J; Andrews, L; Korbel, D; King, E; Fletcher, H; Andersen, R; Bejon, P; Thompson, F; Dunachie, S; Edele, F; de Souza, J; et al. (2005)
Understanding the regulation of immune responses is central for control of autoimmune and infectious disease. In murine models of autoimmunity and chronic inflammatory disease, potent regulatory T lymphocytes have recently been characterized. Despite an explosion of interest in these cells, their relevance to human disease has been uncertain. In a longitudinal study of malaria sporozoite infection via the natural route, we provide evidence that regulatory T cells have modifying effects on blood-stage infection in vivo in humans. Cells with the characteristics of regulatory T cells are rapidly induced following blood-stage infection and are associated with a burst of TGF-beta production, decreased proinflammatory cytokine production, and decreased antigen-specific immune responses. Both the production of TGF-beta and the presence of CD4+CD25+FOXP3+ regulatory T cells are associated with higher rates of parasite growth in vivo. P. falciparum-mediated induction of regulatory T cells may represent a parasite-specific virulence factor.